Gender inclusion and sustainable development in Africa - Vanessa Tchamyou; Ofeh M. Edoh (African Governance and Development Institute (AGDI), 2022)
This study investigates how ameliorating gender inclusion affects sustainable development in Africa over the period 2000-2019 in 42 African countries. It argues that enhancing gender inclusion in all sectors of society promotes and sets a better pace for the attainment of sustainable development in Africa. The gender inclusion variable used is the females employed as a ratio of the working-age. The study employs the Generalized Method of Moments as the main analysis method alongside the Ordinary Least Squaresmethod. It is expected that gender inclusion substantially affects sustainable development in Africa and subsequently, adequate measures should be taken into consideration to boost gender inclusion such as promoting financial inclusion, engaging inclusive education, and engaging inclusive participation in decision making processes at the level of policy making.
Keywords: J16; Q01; O55; 330; Gender inclusion; sustainable development; Africa